Implikatur dan Eksplikatur Percakapan Lokadrama â€œLara Atiâ€ Karya Bayu Skak (Kajian Pragmatik) - Sholihah, Alvia Mustafidatus; Rumilah, Siti (Universitas Suryakanca, 2023)
This article will discuss the context of the implications and explications of the language spoken in an early episode of a film/lokadrama by a YouTuber who is also a Bayu Skak actor. The data were analyzed with Grice's theory regarding explicators and implicatures. The research method used is descriptive qualitative. The film